IDENTIFICATION OF THE COVID-19 DISTRIBUTION AREA ON THE ISLAND OF KALIMANTAN USING THE K-MEANS SPATIAL CLUSTERING METHOD - Fabian Valerian; Sri Yulianto (Jurnal Teknik Informatika (Jutif), 2022)
Based on the map of the spread of COVID-19 in Indonesia, Kalimantan Island is the second island with the number of COVID-19 distributions after Java Island. The purpose of this study is to provide information to the entire community and government, especially the Kalimantan region regarding the clustering of the spread of COVID-19. The K-Means algorithm method used in the grouping is based on data on positive, recovered, and deceased people collected by each province on the island of Kalimantan, then a geographic information system (GIS) is applied in mapping to display the clustered distribution area of ​​each district on the island of Kalimantan. The result of this research is that the k-means algorithm is able to classify data with low, medium, and high distribution levels so that later the distribution area can be mapped using GIS based on the results of the clustering. With the results of this application, it is hoped that it can be used as information for the government and also the public to think about what efforts should be made if bad things happen later, based on the level of spread to be used as a priority scale in controlling the spread of the COVID-19 virus.